ANALISIS PENERAPAN PSAK 50 DAN PSAK 55 ATAS CADANGAN KERUGIAN PENURUNAN NILAI - Husain, Yusni; Sondakh, Jullie J.; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
The application of the new accounting standards that are influential in the banking convergence with International Financial Reporting Standards and International Accounting Standards discussed in (IAS) 39 on recognition and measurement of financial instruments. Financial Accounting Standards Board issued Statement of Financial Accounting Standards (SFAS) 50 and 55 of the Presentation, Recognition and Measurement of Financial Instruments will be effective on January 1, 2012. Allowance for Impairment (Impairment Loss) is derived from the value of the amount to be recorded at recoverable value of the asset. This research was conducted at PT. Bank Mandiri Unit 1 Datulolong Lasut Manado (Persero) Tbk . The purpose of this study was to determine the extent of the application of SFAS 50 and SFAS 55 to the recognition, measurement and presentation of the allowance for impairment losses PT. Bank Mandiri Unit 1 Datulolong Lasut Manado (Persero) Tbk. The results suggest the application of SFAS 50 and SFAS 55 top Allowance for Impairment Losses by PT Bank Mandiri Tbk. compliance with applicable standards.The process of recognition of Allowance for Impairment Losses at amortized value using the effective interest rate. Measuring the level of collective impairment for financial assets is calculated based on the loss historical collectively. Presentation of receivables in the financial statements is the value after deducting the allowance for impairment losses.